Reduction in the level of risk consciousness among mortgagors - Wechta, Przemysław (Economy Today: An Interdisciplinary Approach to Contemporary Economic Challenges, 2016)
The aim of this article is to analyse risk reduction mechanisms that are used by mortgagors. Two basic types of mortgage borrowers were identified: those with low creditworthiness and those with high creditworthiness. A qualitative method was used in the study based on in-depth interviews that were conducted with 20 mortgagors, which made it possible to provide a typologically representative picture of the risk reduction mechanisms used by this group. Finally, two strategies were identified, i.e. the imitation strategy and the professionalization strategy, as well as two effects that are also aimed at reducing the risk.